Fractal model of regional university complexes - I. D. Belonovskaya; V. V. Baranov (Moscow Polytechnic University, 2022)
The methodology of fractal as a self-similar structure for the analysis and a choice of productive models of university complex development is offered. In this regard, the classification of university complex structures on the basis of a fractal is presented. The matter concerns the similarity of the head and filial organizations. It is established that the fractal university structure promotes economic efficiency, self-organizing, self-restoration, availability and openness of continuing education in the region territory, the achievement by the filial organizations of university education level, and also formation of their competitive resource.